Introduction - Smołucha, Janusz; Wróbel, s. Elżbieta Elena; Graff, Tomasz (Rocznik Filozoficzny Ignatianum, 2023)
We are offering you a new issue of The Ignatianum Philosophical Yearbook. It is almost entirely devoted to Mikołaj Zebrzydowski. The state of research on him is outlined in the first article by Elżbieta E. Wróbel and Tomasz Graff. In a separate article, the latter author also presents issues related to the development of Florian Zebrzydowski’s estate as his political importance grew at the court of King Sigismund Augustus. Special emphasis was placed on the case study method here. The author analyzes Zebrzydowski’s acquisition of property in Radocza near Wadowice, showing the prospect of the need for further research into the growth of the estate of Florian Zebrzydowski and his family. The article concludes with an appendix, including an edition in Latin and a Polish translation of the document, in which “Sigismund Augustus grants Florian Zebrzydowski the right to build a dam on the Skawa River and to run water from there through a moat across the area of the Wadowice estate to build fish ponds in the Radocza estate.”